Four Eremophil-9-en-8-one Derivatives from Cremanthodium stenactinium Samples Collected in China - Chiaki Kuroda; Motoo Tori; Xun Gong; Yasuko Okamoto; Mayu Ichihara; Yoshinori Saito (Molecules, 2011)
Two samples of Cremanthodium stenactinium (Asteraceae) were collected in Sichuan Province, China. From the ethyl acetate extracts of the roots, three new eremophilane-type sesquiterpenoids and one new trinoreremophilane compound were isolated, together with other known eremophilanes. Their structures were determined based on the spectroscopic data. This is the first report of isolation of eremophilane-type compounds from the genus Cremanthodium.